2000
DOI: 10.1111/j.1471-0528.2000.tb10394.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal height and external pelvimetry to predict cephalopelvic disproportion in nulliparous African women: a cohort study

Abstract: Objective To assess external pelvimetry and maternal height, as predictors of cephalopelvic disproportion.Design Prospective cohort study.Setting Four hospitals in Zaire.Population Six hundred and five nulliparous women.Methods Maternal height and external pelvimetry were assessed during the third trimester antenatal visit. Cut off values for considering women at risk for cephalopelvic disproportion were height < 150 cm and external pelvic distances < 10th centile for the population. Logistic regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 20 publications
11
70
1
7
Order By: Relevance
“…Gestational age at birth was defined as the number of completed weeks of gestation based on the estimated delivery date in the clinical records. Consistent with previous studies, 13,14 the operational definition of caesarean section indicated for cephalopelvic disproportion (CPD) in our study was based on presumed CPD, and included caesarean sections indicated for dystocia, failure to progress, and failed vacuum extraction or forceps delivery, but excluded those indicated for fetal distress, breech and other types of malpresentation, and failed induction. Maternal and early neonatal deaths were defined as intra-hospital deaths that occurred on or before the eighth day postpartum and seventh day after delivery, respectively.…”
Section: Data Collectionsupporting
confidence: 66%
“…Gestational age at birth was defined as the number of completed weeks of gestation based on the estimated delivery date in the clinical records. Consistent with previous studies, 13,14 the operational definition of caesarean section indicated for cephalopelvic disproportion (CPD) in our study was based on presumed CPD, and included caesarean sections indicated for dystocia, failure to progress, and failed vacuum extraction or forceps delivery, but excluded those indicated for fetal distress, breech and other types of malpresentation, and failed induction. Maternal and early neonatal deaths were defined as intra-hospital deaths that occurred on or before the eighth day postpartum and seventh day after delivery, respectively.…”
Section: Data Collectionsupporting
confidence: 66%
“…Short maternal height was previously reported as a risk factor for CS and shoulder dystocia, likely due to cephalopelvic disproportion (CPD) [27,28,29]. In addition, a large BPD of the newborn was associated with CPD [30].…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to predict which maternal pelvis bares the tendency for CPD and dystocia have been made [2][3][4], suggesting nulliparity [2,3,5], fetal macrosomia, epidural analgesia [6], hydramnios, hypertensive disorders and gestational diabetes mellitus [2,[7][8][9][10][11][12] as risk factors for second stage of labor arrest. Measurement of the intertrochanteric distance and transverse diagonal of Michaelis sacral rhomboid area have been suggested as screening procedure in remote areas [13,14]. Clinical pelvimetry is a fading skill, and X-ray pelvimetry was not proven eVective in predicting CPD and is not recommended for ruling out dystocia due to CPD [1,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%